What Math Matters? Types of Mathematics Knowledge and Relationships to Methods Course Performance. Issue 3 (2nd July 2016) - Kajander, Ann; Holm, Jennifer
ABSTRACT: This study investigated the effect of a departmental focus on enhanced mathematics knowledge for teaching on overall performance in upper elementary mathematics methods courses. The study examined the effect of performance on a new course in mathematics for teaching on performance at the methods course level. In addition, the effect of performance on a high-stakes test of general elementary-level mathematics content knowledge was explored. Mathematics knowledge for teaching was found to be a highly significant predictor of first semester methods course performance, arguably pedagogical content knowledge, whereas knowledge of the general elementary mathematics content appeared less related.